Study on Alpha Rhythms Response to 10 Hz Flicker Is Wavelength Dependent - Francesco Ferro Milone; Antonio Tullio Minelli; Roberto Cian (Research Developments in Science and Technology Vol. 1, 2022)
Since Adrian and Metthew [1], light may be considered the dominant stimulus for the brain. This statement is con- firmed after the discovery of the suprachiasmatic nucleus (SCN) that regulates the master biological clock [2]. In 1998 the discovery of photopigment melanopsin in the ganglion cells of the retina, give new insight in the importance of the light in the pathophysiology of the brain [3]. We have studied the effect of flashing at 10 Hz with LED light of different wavelength on the response of the alpha system. We have shown that this response, consistent with the drive of the frequency and the augmentation of the voltage of the alpha rhythms, is far more significant with the RED-LED than GREEN-LED or BLUE-LED or WHITE-LED (three-chrome) light flashing. We stem the hypothesis that the amplitude increase and phase reset of the alpha waves produced by RED-LED flashing at 10 Hz may be due either to photobiomodulation on the cytochrome c oxidase [4,5] and/or of the photopigment melanopsin, at the level of the retinal ganglion cells, that reinforce the incoming cone-LHC signal and therefore the projection to the SCN [6] or to reinforcement of postsynaptic short term responsiveness, in retinal cone-LHC synapse, due to repetitive stimulation [7,8] or both. We may speculate that the increase of amplitude and phase reset of alpha rhythms, due to flashing at 10 Hz, is primarily modulated in the retina. The involvement of alpha rhythms may promote a deeper understanding of haw phase synchronization support the flexibility of interaction between memory systems and may yield new insight into the function of phase synchronization in general.